2003
DOI: 10.1210/jc.2002-021820
|View full text |Cite
|
Sign up to set email alerts
|

Successful Pregnancy after Bromocriptine Therapy in an Anovulatory Woman Complicated with Ovarian Hyperstimulation Caused by Follicle-Stimulating Hormone-Producing Plurihormonal Pituitary Microadenoma

Abstract: Gonadotropin-producing pituitary adenomas are extremely rare in reproductive-age women. We report here a case of gonadotroph microadenoma with ovarian hyperstimulation. It was found in a 29-yr-old infertile Japanese woman with enlarged multicystic ovaries. The patient had an elevated basal serum estradiol level (up to 6755 pM, or 1840 pg/ml). Serum FSH and prolactin were mildly elevated (15.4 IU/liter, 1.4 nM or 31.4 ng/ml), whereas LH was low (0.5 IU/liter). The FSH level was paradoxically elevated in respons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(25 citation statements)
references
References 29 publications
0
25
0
Order By: Relevance
“…Dizon and Vesely reported a 61-year-old male who showed high plasma levels of FSH, LH, PRL and total T [10]. In addition, some reports showed female cases who showed high levels of FSH and estradiol [11][12][13]. Moreover, Shimon et al reported a case of a 28-year-old female with a high concentration of FSH and a normal level of estradiol [14].…”
Section: Discussionmentioning
confidence: 99%
“…Dizon and Vesely reported a 61-year-old male who showed high plasma levels of FSH, LH, PRL and total T [10]. In addition, some reports showed female cases who showed high levels of FSH and estradiol [11][12][13]. Moreover, Shimon et al reported a case of a 28-year-old female with a high concentration of FSH and a normal level of estradiol [14].…”
Section: Discussionmentioning
confidence: 99%
“…In theory, one possible medical treatment would be the administration of a GnRH analog which would decrease FSH levels, thereby leading to resolution of OHSS; however, reports have actually shown a paradoxical increase in gonadotropin secretion in response to this treatment, 4,[15][16][17][18][19][20] and in one case OHSS was induced after initiation of GnRH therapy with dramatic increases in FSH and estradiol levels. 21 There are three reports of patients with OHSS who were initially treated medically.…”
Section: Treatment and Managementmentioning
confidence: 99%
“…Eventually, however, the adenomas continued to grow and were resected, showing positive immunostaining for LH in two cases and for FSH in one case. 15,22 After resection of a pituitary adenoma, patients are monitored annually with MRI, looking for evidence of a possible recurrence. Patients should also undergo hormonal testing 3 months after surgery to assess whether hypo-pituitarism is present.…”
Section: Treatment and Managementmentioning
confidence: 99%
“…Baseline concentrations of gonadotropin are elevated in 30-50% of gonadotroph adenoma patients, and may result in ovarian hyperstimulation and dysgenesia (28)(29)(30)(31). In previous clinical treatment of gonadotroph adenoma patients with TMZ, changes in gonadotropin levels before and after drug administration were not evaluated (15,16).…”
Section: Discussionmentioning
confidence: 99%